The Roots of Violence in the Rivalry between Football Club Fans and Supporters Using the ABC Triangle Theory of Johan Galtung - Mochamad Ziaul Haq; Andhika Yudhistira (TEMALI : Jurnal Pembangunan Sosial, 2022)
Sport is universal, loved by many people in almost all countries worldwide. As a sport that can be played by many people from all walks of life, football has the potential to be a sport capable of bringing about a spirit of unity and solidarity in a society. However, football can sometimes spark conflict and violence. Excessive football enthusiasm can lead football fans and supporters to become anarchistic and assault individuals who support other teams. This can result in material damages, injuries, and even the loss of life. This essay will examine football fanaticism and football fan violence. Using the ABC conflict triangle theory introduced by Johan Galtung, researchers will analyze how attitudes, behaviors, and contradictions that fans and supporters of football clubs own can trigger football fanaticism and violence. The researchers concluded that these three factors played a role in the outbreak of violence, coupled with other factors such as educational level and socio-economic conditions. The researcher believes that the government, through football organizations, can play a role in suppressing football fanaticism and preventing violence from occurring before, during and after football matches are held. As the core and main part of football, fans and supporters of football clubs must be self-aware and try to be more rational, calm, and not easily provoked to make football a sport that truly unites and is full of solidarity.